Peer assessment: a general review / Akma Hidayu Dol @ Abdul Wahid and Rafizan Abdul Razak - Dol @ Abdul Wahid, Akma Hidayu; Abdul Razak, Rafizan (Universiti Teknologi MARA, Negeri Sembilan, 2023)
What is the first thought that comes to mind when the course assessment requires students to assess each other’s teamwork skills? Many believe that the main issue related to peer assessment is that the majority of students are overly generous to give higher scores to their friends, in the hope that the same favor will be returned to them. As a result, a non-performer will take credit for other’s works. In some instances, though, the students will do the exact opposite, giving their friends who are good team players a lower score and making negative remarks. We briefly reviewed the peer assessment data of our diploma and degree students who were registered for the introductory Financial Accounting and Reporting courses in the recent semester.